The diachrony of negation - Mosegaard Hansen, Maj-Britt; Visconti, Jacqueline, 1966- (Studies in language companion series, 2014)
Labov's idea that the vernacular is the most stable variety of a language raises questions especially where languages of wider communication are concerned. Whether the vernacular practices of a language's geographical varieties are convergent synchronically and historically can be established by looking at particular variables. One such variable is investigated in this paper on the co-occurrence of a clausal negator with a n-word (e.g. I did n't do nothing, i.e. anything). The quantitative study of negative doubling in Quebec and France historical and contemporary ve.